Pengaruh Kapabilitas Dinamis Dan Kapabilitas Inovasi Terhadap Keunggulan Kompetitif - Zatia Zatia; Fitri Kumalasari; Almansyah Rundu Wonua (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
This study aims to determine: (1) The effect of dynamic capabilities on competitive advantage case studi UMKM Kabupaten Kolaka. (2) The effect of innovation capability on competitive advantage case studi UMKM Kabupaten Kolaka.(3)the influence of dynamic capabilities on innovation capabilities as a mediating (intervening) variable in case studies UMKM Kabupaten Kolaka. this research is an explanatory research model with a Quantitative approach. Data collection in this study used literature study and questionnaire distribution. The population of this study were all UMKM of Kolaka Regency. While the sample of this study were 55 respondents using purposive sampling technique.. Testing research instruments employed validity and reliability tests by using SPSS 25.0. The data analysis technique used in this study is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) wich measurement model test (outer model) and structural model testing (inner model) with Smart PLS 4.0. Based on the results of the study, it is known that there is a positive and significant influence between the dynamic capabilities variable on competitive advantage Behavior, this is indicated by the P-Value of 0.005. And the innovation capability variable also has a positive and significant effect on competitive advantage, this is indicated by the P-Value of 0.000. And the dynamic capabilities on innovation capability as mediating (intervene) variable also has a positive and significant effect